Job Satisfaction in Social Enterprises and Socially Responsible Firms - Litwiński, Michał (Studia Oeconomica Posnaniensia, 2015)
The managers of organisations pay more and more attention to the job satisfaction of their employees due to the influence of satisfaction on staff's productivity and loyalty. The literature lacks a comparable analysis of the level of job satisfaction in different subjects. Therefore a problem identified in the article is job satisfaction in social enterprises and private firms that are socially responsible. The topic is especially interesting as both types of subjects create social value, but each of them treat its meaning in a different way. The purpose is to verify the thesis that social value realisation by the described organisations described is not always associated with the same results in job satisfaction. The basis of the article is a complex literature analysis. The author also considered the research in the context of the level of job satisfaction l in particular types of organisations. The article consists of three parts. In the first section the author defines basic concepts, which are studied in following analysis. The subsequent two parts include an analysis of the level of job satisfaction in the types of categories considered. In the section regarding enterprises that take socially responsible actions special attention was paid to the perception of employees with regard to these actions. The article presents a summary of the important assumptions as a conclusion.